Bacteroides fragilis NCTC9343 Produces at Least Three Distinct Capsular Polysaccharides: Cloning, Characterization, and Reassignment of Polysaccharide B and C Biosynthesis Loci - Coyne, Michael J. (American Society for Microbiology, 2000)
Bacteroides fragilis produces a capsular polysaccharide complex (CPC) that is directly involved in its ability to induce abscesses. Two distinct capsular polysaccharides, polysaccharide A (PS A) and PS B, have been shown to be synthesized by the prototype strain for the study of abscesses, NCTC9343. Both of these polysaccharides in purified form induce abscesses in animal models. In this study, we demonstrate that the CPC of NCTC9343 is composed of at least three distinct capsular polysaccharides: PS A, PS B, and PS C. A previously described locus contains genes whose products are involved in the biosynthesis of PS C rather than PS B as was originally suggested. The actual PS B biosynthesis locus was cloned, sequenced, and found to contain 22 genes in an operon-type structure. A mutant with a large chromosomal deletion of the PS B biosynthesis locus was created so that the contribution of PS B to the formation of abscesses could be assessed in a rodent model. Although purified PS B can induce abscesses, removal of this polysaccharide does not attenuate the organism's ability to induce abscesses.